Reproductive performance of Jamunapari crossbred using frozen semen (Bangladesh Journal of Animal Science, 2023)
Artificial insemination (AI) is modern techniques to introduce better and new genetic at the small holder farmer level by using frozen for livestock development. The aimed of the present study to popularization of goat’s artificial insemination to increase goat production with improved genetic merit by assessing the productive and reproductive traits using Jamunapari frozen semen.  The study has been conducted in ten upazila namely Paba, Bagha, Nachal, Chapai sador under Rajshahi region and Birampur, Parbotipur, Fulbari, Kaliganj, Ulipur, Kawnia upazilas under the Rangpur regions. Artificial insemination has been performed in 260 numbers of does. The semen samples initially qualified for freezing was frozen as per the protocol standardized in BRAC bull station, stored in liquid nitrogen (LN2) having the post thaw motility of 50% and were later used for AI. The service per conception was 1.10 in the present study. Moreover, we found that overall conception rate was 67.1%. The average birth weight of male and female kids was 0.98 and 0.95 kg, respectively. In the present study kidding produced single, twins and triplets in 37.7, 50.65 and 11.69% of cases, respectively. The average post-partum heat period was 76.5 days. The results indicated frozen semen AI could successfully be used for preservation, conservation and propagation in Jamunapari goats.Bangladesh Journal of Animal Science 52 (3): 85-87.